OPTIMASI EKSTRAKSI MINYAK BSFL (HERMETIA ILLUCENS) DENGAN METODE MICROWAVE ASSISTED EXTRACTION (MAE) SEBAGAI BAHAN BAKU BIODIESEL - Rohmanna, Novianti Adi; Deoranto, Panji; Arwani, Muhammad; Majid, Zuliyan Agus Nur Muchlis (BPFP Faperta UNIB, 2024)
Black soldier fly (BSF) is an insect to reduces organic matter and produces biomass insects with crude fat of 20.09% -28.89%. BSF larvae have a high lipid content compared to other flies as raw material for making biodiesel. This research aimed to determine the optimum condition of BSF’s lipid extraction process using MAE. The method was the response surface method (RSM) central composite design (CCD) with two factors and three response variables. The research factors were extraction temperature (60, 75, and 90 0C) and extraction time (20, 30, and 40 minutes). Identification of the response variables measured were oil yield, free fatty acids (%FFA), and acid number of black soldier fly (BSF) larvae oil with limits according to SNI 7182:2015. The optimal solution resulted from the treatment level with an extraction temperature of 60 0C with an extraction time of 37.69 minutes. The higher temperature treatment significantly increased the oil yield, but on the other hand, it also increased the free fatty acid content and acid number in the larvae oil. The longer extraction time significantly increased the resulting oil yield but could also significantly increase the free fatty acid content and acid number. The predicted results for the optimal solution response to oil yield was 30.22%, free fatty acid was 3.26%, and the acid number was 6.48 mgKOH/g. The results generated from the data validation of each oil yield response was 29.28%, free fatty acid was 3.29% and the acid number was 6.54 mgKOH/g.